2018
DOI: 10.1016/j.jmapro.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Particle migration and surface modification on Ti6Al4V in SiC powder mixed electrical discharge machining

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(26 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…The traces of oxygen (O), carbon (C) and Si confirms particle migration from dielectric to surface. As a result, the surface chemistry and porous recast layer fabricated in this research work are considered as highly favorable for biomedical applications as previously reported in [6,36,41,43]. The decomposed elements formed oxides and carbides are highly likely to enhance surface hardness and bio activity.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…The traces of oxygen (O), carbon (C) and Si confirms particle migration from dielectric to surface. As a result, the surface chemistry and porous recast layer fabricated in this research work are considered as highly favorable for biomedical applications as previously reported in [6,36,41,43]. The decomposed elements formed oxides and carbides are highly likely to enhance surface hardness and bio activity.…”
Section: Resultssupporting
confidence: 60%
“…Moreover, the Si traces in craters confirms the material migration phenomenon controlling machined surface quality. A similar study [36] on Ti6Al4V reported ~4.2 μm at 2A current. However, the current study has improved the surface results by almost 50%.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The surface integrity of the machined specimen is evaluated in the purview of surface morphology and topographical features [11]. The impact of SiC powder concentration on surface topography, particle deposition, and subsurface structures in the PM-EDM of Ti-6Al-4V-ELI work material was studied, and it was observed that a high suspended particle concentration in dielectric liquid enhance the material transfer mechanism in a particulate form [12]. Flushing mode plays an important role in any EDM operation.…”
Section: Introductionmentioning
confidence: 99%